Action Observation and Effector Independency - Betti, Sonia; Deceuninck, Marie; Sartori, Luisa; Castiello, Umberto (Frontiers in Human Neuroscience, 2019)
The finding of reasonably consistent spatial and temporal productions of actions across different body parts has been used to argue in favor of the existence of a high-order representation of motor programs. In these terms, a generalized motor program consists of an abstract memory structure apt to specify a class of non-specific instructions used to guide a broad range of movements (e.g., “grasp”, “bite”). Although a number of studies, using a variety of tasks, have assessed the issue of effector independence in terms of action execution, little is known regarding the issue of effector independence within an action observation context. Here corticospinal excitability of the right hand’s First Dorsal Interosseous (FDI) and Abductor Digiti Minimi (ADM) muscles was assessed by means of single-pulse transcranial magnetic stimulation (spTMS) during observation of a grasping action performed by the hand, the foot, the mouth, the elbow, or the knee. The results indicate that observing a grasping action performed with different body parts activates the effector typically adopted to execute that action, i.e. the hand. We contend that, as far as grasping is concerned, motor activations by action observation are evident in the muscles typically used to perform the observed action, even when the action is executed with another effector. Nevertheless, some exceptions call for a deeper analysis of motor coding.